A Novel Lightweight Key Management Scheme for Patient Data Privacy on Body Sensor and Cloud based Healthcare Service (International Journal of Advanced Research in Computer Science, 2017)
The healthcare networks consist of the wireless sensors to monitor the patient’s health, hence called wireless body area networks (WBANs). The wireless sensors collect and transmit the health information to the healthcare management servers, which are usually hosted on the cloud platforms. The cloud platforms based healthcare management services offer high scalability and robustness in terms of response time, resource and data handling, but prone to various types of information leakage attacks due to the higher level of exposure to the outer world. The proposed model is based upon the secure tunnel based on randomized authentication & key management service, which is designed as the lightweight key management scheme for WBANs to protect the patient data privacy during the transmissions. The scheme aims at providing the higher level of security while keeping the battery consumption at the lowest possible level for the key management service.Keywords: Data Transmission time; High Entropy Keys; Key Management; Patient data privacy; Randomized Key generation.